Electrolyte imbalance in hospitalized children with infections - a tertiary care Experience - Hassan, Mahmuda; Khan, Masuma; Mukti, A; Roy, S; Begum, Marium; Ferdous, Zannatul; Yasmeen, B H Nazma (Northern International Medical College Journal, 2024)
Background: Electrolyte imbalances are a common finding in hospitalized children, especially those with infections. Infections interfere with the body's normal fluid and electrolytes balance as well as various factors also contribute to electrolyte imbalances. Sometimes medicine used in the treatment of infections contributes in electrolyte abnormalities. Usually, the types of electrolyte abnormalities found among the hospital admitted children with infections are Hyponatremia, Hypernatremia, Hypokalemia, Hyperkalemia, Hypocalcemia etc. Objective: To find out the types of electrolyte imbalance in hospitalized children with infection. Methodology: This is a hospital based cross sectional study conducted from 1st April 2019 to 31st March 2020 at Ad-Din Women’s Medical College Hospital. A total of 120 children who met the inclusion criteria were enrolled for the study. Children aged 1 to 12 years, who were admitted into Pediatric ward with clinical diagnosis of septicemia with septic shock or with different bacterial infections were included in this study. Children with non-infectious diseases, Syndromic children, with prolonged medications like diuretics, steroids, chronic diseases, kidney diseases, protein energy malnutrition were excluded from this study. During admission, all suspected cases of infections were advised to do sepsis screening and serum electrolytes (serum sodium (Na+), serum potassium (K+), sometimes serum calcium (C-). At the time of admission, who were not investigated for electrolytes; they were also advised for electrolytes (several times) during his/her hospital stay particularly who were on intravenous fluid for more than 3 days without any enteral feed. Data were collected by clinical interview, physical examination and lab investigations report using a pretested structured questionnaire. All data was entered in a master chart in Microsoft Excel sheet and was analyzed in SPSS 21.0 software. Result: Total 120 children were enrolled in this study, age ranges from 1 month to 12 years. Male 68(56.66%) and female 52(43.33%) with male female ratio 1.3 :1. Infants from 1 month to 1 year 68(56.66%), from 1 year to 5 year 38(32.66%) and 5years up to 12 years 14 (11.66%). Children had the following clinical presentations -fever in 52(43.33%) cases , reluctant to take feed 32(26.66%) vomiting 52 (43.33%), lethargy 23(19%), loose motion 60(50%), abdominal pain 14(11.66%), cough and respiratory distress 20(16.66%),tetany/convulsion 21(17.5%), unconsciousness 10(8.33%). History of taking in appropriately prepared ORS 17(14.66%) and concentrated ORS were present in 11(9.1%) cases. Clinical diagnosis was septicemia with or without septic shock, with blood culture positive10(8.3%), diarrhea/invasive diarrhea 58(48.33%), enteric fever 10(8.3%), pneumonia 6(5%),UTI/ Urosepsis 4(3.33%), Meningitis/ meningoencephalitis 8(6.66%), TBM 2(1.6%), dengue fever 6(5%), probable bacterial infections 8(6.66%) Among 120 cases serum Na <135mmol/l were in 34(28.33%) cases, from 135 to 145mmol/l were in 38(31.66%) but they had isolated hypokalemia. Mild hypernatremia were in 18(15%), moderate hypernatremia was in 24(20%) and severe hypernatremia were in 6(5%). Hypokalemia found in 70(58.33%)cases, Hyperkalemia present in 8(6.66%) and normal potassium were in 42(35%) cases, but they had isolated Hypernatremia or Hyponatremia. Chloride levels between 99 to 106mmol/l were in 40(33.33%) cases,<99mmol/l were in 30(25%) cases and >105mmmol/l were in 50(41.66%) cases. Conclusion : Electrolyte imbalances are common in children with different types of infections specially in diarrhea with severe dehydration. Specific symptoms of electrolyte abnormality often merged with the underlying disease. A high index of suspicion is very important for identification of electrolyte imbalance. Northern International Medical College Journal Vol. 13 No. 1-2 July 2021-January 2022, Page 588-593